Dedicado à glória de Deus e ao progresso humano: a gênese protestante da Universidade Federal de Lavras-UFLA (Lavras, 1892-1938) - Rossi, Michelle Pereira da Silva (2010)
This thesis is positions in the field of the History of the Educational Institutions, and presents the education project of the Agricultural School of Lavras, begun by the mission board of the Presbyterian Church of the United States in 1908 (East Brazil Mission), which is the beginning of the Federal University of Lavras UFLA. The thesis presents itself as a debate of the relationship between religion and progress, as in regard to the establishment of values in the category of progress and, in the same way, as was attributed to the ideals of the Protestant evangelization. Therefore, it is the objective to explain how the establishment of the Agricultural School of Lavras, referred to by the missionaries as the missionary school, configured itself as an important means of protestant evangelization, while in the same way meetings the agricultural educational demands in the state of Minas Gerais under the ideals of the modernization of the field. In developing the research the following procedures were utilized: biographical research referring to the fundamental history of Protestantism, the history of Brazilian education, and the research of the documentation of the implantation of the Presbyterian educational process in Lavras: Prospects of the Evangelical Institute, Rules and Regiments of the Agricultural Studies of the Agricultural School of Lavras, Visitor Registration Book, letters, and others. In an attempt to localize such educational principles, the chronological plan took place during the first years of the Republic of Brazil, 1892, when the Presbyterian missionaries established residency in Lavras. In reference to the limit date, 1938, when the Agricultural School of Lavras changes name and becomes the Superior School of Agriculture of Lavras (E.S.A.L). In this study it was privileged the project of agricultural education in Minas Gerais, which can be divided in two important moments: The first, beginning in 1903, is characterized by the investment in schools of elementary level for agricultural workers; during this period, the educational politics of João Pinheiro mark such initiatives, once the level of secondary and superior education were in the hands of private initiatives. The second moment is marked by state initiatives, beginning in the 1920 s, when the investment of secondary and superior level of agriculture occur; the mark of this moment is the creation of the Superior School of Agriculture and Veterinary of the state of Minas Gerais ESAV. The influence of the North-American academic culture on the practical educational of the schools deserves eminence: the intuitive methods, the extension project, the associations, the sports. As results, we understand that the history of the School of Agriculture of Lavras is marked by two phases: the first is the moment when the school is inaugurated as an elementary education, being equipped at middle level according to the regulation of the Agricultural education in 1911. The second, in 1917, when the school is officially recognized by the government of Minas Gerais; from whence comes the effort to equip itself to the superior level, acquiring its own buildings, whose apex is the recognition as a school of superior studies in 1936 by the Federal Government. The link between education and evangelism met the Presbyterian ideals, making it possible to identify that Protestantism of influence or the evangelization indirectly (via Education), embraced by the West Brazil Mission in Lavras, sought to portray a model of a school that successfully reached the religious and social principles, for the Protestantism was presented as a religious propulsory to the progress, evidencing the objectives that directioned the theme of the Gammom institution, Dedicated to the Glory of God and to human progress: To teach was to transmit not only the rational learning directions to the development of agriculture by means of the utilization of machinery, by policultural, by studying the soil; but also the education of protestant religious values.